Prevalence of and factors associated with obesity among secondary school students in Petaling district, Selangor - Garba, Jamila Abubakar (2013)
Obesity is one of the public health problems that affects all ages in both developing and developed countries with an increasing prevalence globally. Obesity in adolescents can continue up to adulthood and increases the chance of developing non-communicable diseases. An analytic cross-sectional study was done among secondary school students in Petaling district to determine prevalence and factors associated with obesity. Sampling with probability proportionate to size was used and 5 schools were selected. Self-administered pretested questionnaires in Bahasa Malaysia were used to capture the socio-demographic characteristics, physical activity, dietary pattern, smoking status and psychological factors (self-esteem & body image). Weight was measured to the nearest 0.1kg using a digital bathroom scale (TANITA model HD-319); height was measured by using SECA body meter model 206 to the nearest 0.1cm.The response rate was 90.7%. The prevalence of obesity among the respondents was 13.7% (95% CI= 12.3, 15.1). Males had a significantly higher prevalence of obesity 15.9% (95% CI= 14.4, 17.4) compared to females with 12.3% (95% CI= 10.94, 13.66). Malay respondents had the highest prevalence of 16.2% (95% CI = 14.68, 17.72), followed by Chinese with 11.5% (95% CI= 10.2, 12.8) and then Indians with prevalence of 10.5% (95% CI= 9.23, 11.77). Those with low physical activity had significantly higher prevalence of obesity than those with high physical activity (χ2 = 237, df = 1, p <0.001). Those with low self-esteem had significantly higher prevalence of obesity than those with normal self-esteem (χ2 = 143, df =1, p <0.001). Prevalence of obesity was also significantly higher among those with body parts dissatisfaction (χ2 = 10, df = 1, p <0.001) and body size dissatisfaction (χ2 = 90, df = 1, p <0.001). However, there was no statistical association between obesity and the dietary patterns (dietary pattern 1 χ2 = 5.919, df= 3, p = 0.116; dietary pattern 2 χ2 = 7.728, 3, p = 0.052; dietary pattern 3 χ2 = 5.923, df= 3, p = 0.115). Logistic regression was used to determine the predictors of obesity and the significant predictors of obesity were gender (Male’s odd ratio (OR) =2.389, 95% CI= 1.7, 3.3, p < 0.001), age (13 to <14 years OR =2.05, 95% CI = 1.1, 3.7, p =0.019; 14 to <15 years OR =2.95, 95% CI = 1.1, 3.6, p = 0.034), low physical activity (OR = 82.8, 95% CI = 45.5, 151.0, p < 0.001), low self-esteem (OR = 7.77, 95% CI = 5.15, 11.71, p < 0.001), body parts dissatisfaction (OR = 1.479, 95% CI = 1.2, 1.9, p = 0.002) and body size dissatisfaction (OR = 4.705, 95% CI = 2.6, 8.5, p < 0.001).In conclusion, this study has identified that the prevalence of obesity is high among adolescents and found to be associated with modifiable risk factors which are low physical activity, low self-esteem and body image dissatisfaction. The findings from this study can be used by policy makers to plan preventive measures to tackle the increasing prevalence of obesity.